CHEST IMAGING FOR EARLY DIAGNOSIS OF COVID-19 ON A PATIENT WITHOUT RESPIRATORY SYMPTOMS: A CASE REPORT - Wahyu Widiastana; Teguh Kristian Perdamaian; Sutaryanu Dermoredjo (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: The Coronavirus 2019 disease (COVID-19) is transmitted through droplet and aerosol from the respiratory tract of an infected person; and fomites from infected linen and surface. On August 1, 2020, in Yogyakarta, there were 741 confirmed positive cases of COVID-19, and it is still possible to increase. In the time of understanding COVID-19, there are many cases with atypical presentation, including gastrointestinal symptoms. Objective: To describe a COVID-19 case without respiratory symptoms and the role of radiology in detecting COVID-19. Case Description: A 55-year-old male patient came to the hospital complaining of nausea and loss of appetite. Based on the results of the physical examination, there was flatulence. Initial investigations revealed a non-reactive SARS CoV 2 IgG and IgM result. Further non-contrast MSCT Thorax showed infiltrates with bilateral sub-pleural posterolateral consolidation, particularly the left, showing typical pneumonia. Multiple blebs were also found, denoting bronchiectasis. Confirmatory RT-PCR result was positive for SARS CoV 2. Conclusion: COVID-19 usually presents with common respiratory symptoms. However, some patients also experience gastrointestinal symptoms that initially were not detected as COVID-19. In time of COVID-19 pandemic, persistent gastrointestinal symptoms in a high-risk patients warrant further chest imaging and RT-PCR of SARS CoV-2 to detect or exclude the possibility of COVID-19 diagnosis.